2020
DOI: 10.3389/fpsyg.2020.01034
|View full text |Cite
|
Sign up to set email alerts
|

Emotional Trajectory at Different Career Stages: Two Excellent Teachers’ Stories

Abstract: The current study aimed to investigate excellent teachers' emotional journey, particularly, the trajectory of emotional experiences and emotional labor strategies at different career phases. The research used a case-study approach to explore the storied experience of two teachers (female and male) who were bestowed the Provincial Excellent Teacher Award. They were close to retirement so they could retrieve emotional experiences from across their entire career. Individual semi-structured interviews were utilize… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
20
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 50 publications
1
20
0
3
Order By: Relevance
“…Specifically, optimistic emotions (e.g., pride and love) from teacher leaders positively and significantly affected teacher trust in colleagues. This result aligns with the studies (Arar and Oplatka 2018 ; Chen and Walker 2021 ) that reported that principals from Israel conveyed their pleasant emotions to create an optimistic school culture. However, teacher trust in principals is the prerequisite to ensuring this transit.…”
Section: Discussion and Future Directionssupporting
confidence: 91%
See 2 more Smart Citations
“…Specifically, optimistic emotions (e.g., pride and love) from teacher leaders positively and significantly affected teacher trust in colleagues. This result aligns with the studies (Arar and Oplatka 2018 ; Chen and Walker 2021 ) that reported that principals from Israel conveyed their pleasant emotions to create an optimistic school culture. However, teacher trust in principals is the prerequisite to ensuring this transit.…”
Section: Discussion and Future Directionssupporting
confidence: 91%
“…It is universally acknowledged that teaching and school leadership are both high-risk jobs (Chen et al 2020a , b ; Riley 2018 ). After being underplayed for decades, research on both teachers’ and principals’ emotions has blossomed recently (e.g., Chen 2020a ; Crawford 2019 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…El estudio de las emociones de las y los docentes ha concitado de manera persistente el interés de los investigadores desde fines del siglo XX (e.g., Chen et al, 2020;Keller et al, 2014;Saric, 2015;Uitto et al, 2015;Xu, 2018;Zembylas & Schutz, 2016). La complejidad de este objeto de estudio puede observarse en la diversidad de aristas investigativas que desde éste se han desarrollado.…”
Section: La Investigación Sobre Emociones En Profesoresunclassified
“…This situation harms the psychosocial and physiological health of school leaders, reciprocally affecting job performance and satisfaction (De Nobile & McCormick, 2010 ). Therefore, school leaders’ emotions and their emotional capabilities increasingly become one of the key aspects in taking a school forward (Chen & Guo, 2020 ; Chen & Walker, 2021 ; Leithwood et al, 2020 ).…”
mentioning
confidence: 99%